Impacts of BMI & IL-4 Genetic Polymorphisms (rs2243250 C/T & rs2227284 A/C) on Iranian Breast Cancer Patients: a Pilot Study - Samanehsadat Shahidi; Zahra Tahmasebi Fard (Fasa University of Medical Sciences, 2022)
Background & Objective: Breast cancer is a phenotypically complex and diverse genetic disease caused by changes in the structure and expression of specific genes. Immune system factors are also involved in the etiology of this neoplasm. This study aimed to evaluate the effect of genetic changes (rs2243250 & rs2227284) on the interleukin 4 gene and body mass index on breast cancer risk in Iranian women. Material & Methods: From women referring to Shohada-Tajrish Hospital, 100 women with breast cancer and 100 healthy women were selected. After blood sampling and DNA extraction, the women's genotypes were determined using the RFLP-PCR technique. The results were evaluated by SPSS software version 21 and chi-square and logistic regression tests. Results: Analysis of the results with different genetic models showed the effect of rs2243250 on breast cancer (p<0.05), but rs2227284 was not associated with breast cancer (p>0.05). People with the CC / TT genotype (polymorphism) were more likely to get breast cancer. Also, the increase in body mass index was significantly associated with both polymorphisms studied. Also, carriers of the TT genotype of rs2243250 polymorphism were more likely to develop breast cancer with aging. Conclusion: Genetic alterations in the IL-4 gene and obesity probably contribute to breast cancer, and carriers of both genetic modifications (CC / TT) are more likely to develop breast cancer.